Analysis of the Implementation of Pencak Silat Learning in Physical Teachers of State High School in Pekanbaru City - Kamarudin, Kamarudin; Sasmarianto, Sasmarianto; Auliyasari, Riska; Nurliani, Lira Dwi (Indonesian Journal of Sport Management, 2025)
The purpose of this study was to determine the implementation of pencak silat learning in physical education teachers of state senior high schools throughout Pekanbaru City. The type of this research is descriptive quantitative. The population in this study were physical education teachers in Pekanbaru Senior High Schools totaling 96 people, the sampling technique used was total sampling so that all populations were sampled. The research instrument used was filling out a questionnaire. Based on the research results, the conclusions obtained in this study are: the implementation of pencak silat learning in physical education teachers of state senior high schools throughout Pekanbaru City is included in the range of 81-100% or in the strong category with a percentage of 92.93%.